Narrowing row spacing and adding inter-block promote the grain filling and flag leaf photosynthetic rate of wheat under enlarged drip tube spacing system - Jing, Jianguo; Qian, Fu; Chang, Xinyi; Li, Zhaofeng; Li, Weihua (Frontiers in Plant Science, 2024)
Enlarging the lateral space of drip tubes saves irrigation equipment costs (drip tubes and bypass), but it will lead to an increased risk of grain yield heterogeneity between wheat rows, adjusting wheat row spacing is an effective cultivation measure to regulate row's yield heterogeneity. During a two-year field experiment, we investigated the variations in yield traits and photosynthetic physiology by utilizing two different water and fertilizer demands spring wheat cultivars (NS22 and NS44) under four kinds of drip irrigation patterns with different drip tube lateral spacing and wheat row spacing. The results showed that under 15 cm equal row spacing condition, after the number of wheat rows served by single tube increased from four (TR4, control) to six (TR6), the NS22 and NS44 exhibited a marked decline in yield, the decline of NS22 (9.93%) was higher than that of NS44 (9.04%); And both cultivars also showed a greater decrease in the grain weight and average grain-filling rate (AGFR) of inferior grains (NS22: 23.19%, 13.97%; NS44: 7.78%, 5.86%) than the superior grains (NS22: 10.60%, 8.33%; NS44: 4.89%, 4.62%). After the TR6 was processed to narrow WRHS (from 15 cm to 10 cm) and add IBS (TR6L: 35 cm; TR6S: 25 cm), the grain weight per panicle (GWP) and AGFR of superior and inferior grains in the third wheat row (RW3) of NS22 and NS44 under TR6L increased significantly by 26.05%, 8.22%, 14.05%, 10.50%, 5.09% and 5.01%, respectively, and under TR6S significantly increased by 20.78%, 9.91%, 16.19%, 9.28%, 5.01% and 4.14%, respectively, the increase of GWP and AGFR were related to the increase in flag leaf area, net photosynthetic rate, chlorophyll content, relative water content, actual photochemical efficiency of PSII and photochemical quenching coefficient. Among TR4, TR6, TR6L and TR6S, for both NS22 and NS44, the yield of TR6S was significantly higher than that of TR6 and TR6L, furthermore, TR6S showed the highest economic benefit.